Use of podcast technology to facilitate education, communication and dissemination in palliative care: the development of the AmiPal podcast. Issue 2 (31st August 2016) - Nwosu, Amara Callistus; Monnery, Daniel; Reid, Victoria Louise; Chapman, Laura
Abstract : Objectives: Podcasts have the potential to facilitate communication about palliative care with researchers, policymakers and the public. Some podcasts about palliative care are available; however, this is not reflected in the academic literature. Further study is needed to evaluate the utility of podcasts to facilitate knowledge-transfer about subjects related to palliative care. The aims of this paper are to (1) describe the development of a palliative care podcast according to international recommendations for podcast quality and (2) conduct an analysis of podcast listenership over a 14-month period. Methods: The podcast was designed according to internationally agreed quality indicators for medical education podcasts. The podcast was published on SoundCloud and was promoted via social media. Data were analysed for frequency of plays and geographical location between January 2015 and February 2016. Results: 20 podcasts were developed which were listened to 3036 times (an average of 217 monthly plays). The Rich Site Summary feed was the most popular way to access the podcast (n=1937; 64%). The mean duration of each podcast was 10 min (range 3–21 min). The podcast was listened to in 68 different countries and was most popular in English-speaking areas, of which the USA (n=1372, 45.2%), UK (n=661, 21.8%) and Canada (n=221, 7.3%) were most common. Conclusions: A palliative care podcast is a method to facilitate palliative care discussion with global audience. Podcasts offer the potential to develop educational content and promote research dissemination. Future work should focus on content development, quality metrics and impact analysis, as this form of digital communication is likely to increase and engage wider society.